Inhibition of mycobacterial arylamine N-acetyltransferase contributes to anti-mycobacterial activity of Warburgia salutaris. - Madikane, V; Bhakta, S; Russell, A; Campbell, W; Claridge, T; Elisha, BG; Davies, S; Smith, P; Sim, E (2007)
In this study, we show that extracts and a purified compound of Warburgia salutaris exhibit anti-mycobacterial activity against Mycobacterium tuberculosis H37Rv and Mycobacterium bovis BCG Pasteur. The extracts did not inhibit growth of Escherichia coli and were not toxic to cultured mammalian macrophage cells at the concentrations at which anti-mycobacterial activity was observed. The extract and pure compound inhibited pure recombinant arylamine N-acetyltransferase (NAT), an enzyme involved in mycobacterial cell wall lipid synthesis. Moreover, neither extract nor pure compound inhibited growth of a strain of M. bovis BCG in which nat has been deleted suggesting that NAT may indeed be a target within the mycobacterial cell. The purified compound is a novel drimane sesquiterpenoid lactone, 11alpha-hydroxycinnamosmolide. These studies show that W. salutaris is a useful source of anti-tubercular compounds for further analysis and supports the hypothesis of a link between NAT inhibition and anti-mycobacterial activity.